2018
DOI: 10.1111/cas.13842
|View full text |Cite
|
Sign up to set email alerts
|

Combination immunotherapy with interleukin‐2 surface‐modified tumor cell vaccine and programmed death receptor‐1 blockade against renal cell carcinoma

Abstract: Immunotherapy may be an effective way to prevent postoperative recurrence of renal cell carcinoma. Streptavidin‐interleukin‐2 (SA‐IL‐2) surface‐modified tumor cell vaccine developed through our protein‐anchor technology could induce specific antitumor T‐cell responses, but this immunotherapy cannot completely eradicate the tumor. These effector T cells highly expressed programmed death receptor‐1 (PD‐1), and the expression of programmed death ligand‐1 (PD‐L1) in the tumor environment also was upregulated after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
(69 reference statements)
0
7
0
Order By: Relevance
“…The efficacy of immunotherapy depends on infiltrated immune cells and the expression of immune checkpoint molecules in the TME ( Zhang et al, 2019 ; Huang et al, 2020 ). Thus, we evaluated the correlation between RNF169 and immune checkpoints and found that high expression of RNF169 was associated with CTLA4 or CD274, indicating that targeting RNF169 may be a potential approach to improve the efficacy of immunotherapy for PAAD.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of immunotherapy depends on infiltrated immune cells and the expression of immune checkpoint molecules in the TME ( Zhang et al, 2019 ; Huang et al, 2020 ). Thus, we evaluated the correlation between RNF169 and immune checkpoints and found that high expression of RNF169 was associated with CTLA4 or CD274, indicating that targeting RNF169 may be a potential approach to improve the efficacy of immunotherapy for PAAD.…”
Section: Discussionmentioning
confidence: 99%
“…109 IL-2 has been combined with a range of other therapies including imiquimod, with a reported 100% intralesional CR rate 110 and anti-PD-1 therapy. 111 The highest CR rate of 5.0% was associated with IL-2 combined with vaccine therapy in RCC. 104 In a separate study, topical daily application of 5% imiquimod cream (Aldara, Bausch, Quebec, Canada) was undertaken for 4 weeks to superficial melanoma lesions, followed by IL-2 injected either intralesionally, subcutaneously or a combination of both, according to three regimens.…”
Section: Systemic and Local Intratumoural Therapiesmentioning
confidence: 96%
“…PD‐1/PD‐L1 mAbs could reverse this immune escape, promote IFN‐γ and IL‐12 expression, and further enhance the cytotoxicity of specific antitumor T cells. 112 Moreover, glutamine‐addicted ccRCC depletes extracellular glutamine and then upregulates HIF‐1α expression, thereby inducing tumor‐infiltrating macrophages to secrete IL‐23. It could promote IL‐10 and TGF‐β expression and then decrease the IFN‐γ, GZMB, and PRF1 expression levels on CD8+ T cells to inhibit their cytotoxicity; thus, IL‐23 inhibitors also have a synergistic effect with PD‐1 mAbs.…”
Section: Mechanisms Affecting Cellular Immunity In Rccmentioning
confidence: 99%